2016
DOI: 10.3233/wor-162253
|View full text |Cite
|
Sign up to set email alerts
|

The effect of loupes on neck pain and disability among dental hygienists

Abstract: Overall, despite no statistically significant differences being detected, this study suggests that wearing loupes appears to have both positive and negative outcomes with regards to physical well-being. As such, further studies are required to more precisely determine the effects of loupes on MSD among dental hygienists, particularly long-term. Dental hygienists with existing neck pain exploring ergonomic equipment may reflect on the findings and consider the potential benefits and risks of wearing loupes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
64
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(68 citation statements)
references
References 33 publications
2
64
1
1
Order By: Relevance
“…1,2,4,5,[7][8][9][10][11]25 This study found improved ergonomic scores with the descriptive analysis of mean ergonomic scores (Table 2), 2X2X2 mixed-design ANOVA (Table 3), and the post-study questionnaire. 1,2,4,5,[7][8][9][10][11]25 This study found improved ergonomic scores with the descriptive analysis of mean ergonomic scores (Table 2), 2X2X2 mixed-design ANOVA (Table 3), and the post-study questionnaire.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…1,2,4,5,[7][8][9][10][11]25 This study found improved ergonomic scores with the descriptive analysis of mean ergonomic scores (Table 2), 2X2X2 mixed-design ANOVA (Table 3), and the post-study questionnaire. 1,2,4,5,[7][8][9][10][11]25 This study found improved ergonomic scores with the descriptive analysis of mean ergonomic scores (Table 2), 2X2X2 mixed-design ANOVA (Table 3), and the post-study questionnaire.…”
Section: Discussionmentioning
confidence: 88%
“…[1][2][3][4][5][6][7][8][9][10][11] Among one group of dentists, 73.9% of respondents reported musculoskeletal pain, even though 59.3% reported an awareness of neutral ergonomic positions. [1][2][3][4][5][6][7][8][9][10][11] Among one group of dentists, 73.9% of respondents reported musculoskeletal pain, even though 59.3% reported an awareness of neutral ergonomic positions.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Among them there are: − Increase of motivation component of sports practicing [25,36] considering students' reactions to physical loads [46]; − Optimization of physical loads' volumes for students, considering their individual fitness [26,40,41,65]; − Reduction of environmental and harmful habits' negative influence [50,51]; − Application of modern and new training methods [61,63]; − Organization of proper pedagogic control in trainings of students with different fitness [28,47]; − Raising of health criteria, considering psychological factors' influence [48,52] and health culture formation [71]; − Implementation of physical education pedagogic technologies in the process of training of students with different nosologies [22,54,59,62]; − Application of health related students' trainings with sport competition elements [57]; − Individual approach in choice of strategy, tactic and methodological provisioning of physical rehabilitation for students with pathologies [45,67]; Important criterion of the listed above approaches to students' health improvement is students' workability. Among approaches to increase students' workability we can name: − Weakening of chronic fatigue under different loads [39,43]; − Determination of motor and sports rank places in students' leisure hierarchy [42]; − Adaptation to physical loads [37].…”
mentioning
confidence: 99%
“…This range is alarming but corroborates similar studies with dentists. 12,14,21,22 Ergonomic aspects are not subject of this study, but it should be mentioned that this positive effect is dependent on a good adjustment with respect to the individual working position. The better near visual performance of the younger group could be expected owing to the presbyopic constraints above an age of 40 years.…”
Section: Discussionmentioning
confidence: 98%